2‐aminoindan‐2‐phosphonic acid alleviates oxidative browning in fresh‐cut lily bulbs. Issue 4 (6th February 2022) - Kan, Juan; Liu, Ying; Hui, Yaoyao; Wan, Bing; Liu, Jun; Qian, Chunlu; Jin, Changhai
Abstract: 2‐aminoindan‐2‐phosphonic acid (AIP) functions as a particular inhibitor of polyphenol biosynthesis in phenylpropanoid pathway. In this study, the role of AIP in browning resistance of fresh‐cut lily bulbs during storage was investigated. Application of 0.5 mmol/L AIP decreased browning degree of fresh‐cut lily bulbs, which was accompanied by reduced total phenolics content (TPC) and enzymes related to enzymatic browning including polyphenol oxidase (PPO), phenylalanine ammonia‐lyase (PAL) and peroxidase (POD). In comparison with the control, AIP efficiently maintained cell membrane integrity and lowered oxidative stress via inhibiting lipoxygenase (LOX) activity and malondialdehyde (MDA) content as well as promoting the activities of superoxide dismutase (SOD), catalase (CAT), and energy‐metabolism related enzymes, thus controlling browning of fresh‐cut lily bulbs. The browning inhibition of AIP was highly correlated with cell membrane structure, energy metabolism and enzymatic browning. These results show that AIP is a potential way to prevent browning of fresh‐cut lily bulbs. Novelty impact statement: The quality and shelf‐life of fresh‐cut lily bulbs are seriously reduced due to tissue browning. This work investigates the effect of AIP on alleviating oxidative browning of fresh‐cut lily bulbs for the first time to our knowledge. The inhibitory effect of AIP on fresh‐cut lily bulbs was highly correlated with cell membrane structure, energy metabolism and enzymatic browning.